The System of Executive Bodies of the Republic of Karakalpakstan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article deals with the content of scientific concepts "Council of Ministers of the Republic of Karakalpakstan", "local government body". "Ministry", "State Committee", provides a classification of the powers of the executive authorities of the Republic of Karakalpakstan taking into account their characteristics and organizational and legal foundations.